Volatile compound changes at Brunfelsia uniflora flower senescence - Colauto, Nelson Barros (2024)
The flower of Brunfelsia uniflora has few studies and no chemical characterization of volatiles by direct extraction via headspace and analysis by gas chromatography coupled to mass spectrometry (HS/GC-MS). This study provides background information on the flower senescence process. The objective of this study was to compare the chemical composition of volatiles from the purple and white flower stages of B. uniflora by HS/GC-MS. The volatile compounds from flowers incubated in headspace vials were analyzed by GC-MS. Oxygenated sesquiterpenes were the majority volatile class. The main volatile compounds for purple flower were trans-nerolidol (16.2%), trans-geranylgeraniol (5.8%), cis-linalool oxide (4.9%), and cis-cis-geranyl linalool (4.4%), and for white flower were trans-nerolidol (26.1%), trans-β-ocimene (9.5%), trans-geranylgeraniol (7.9%), and trans-γ-bisabolene (3.1%). Our results increased the knowledge of the types of volatile chemical compounds at different maturation stages of B. uniflora flower.